Unveiling B7/CD28 family proteins in hepatocellular carcinoma: insights into communication and prognostic significance - Cai, Yan; Liu, Xiaodi; He, Tao; Xu, Yangming; Chen, Shuxian; Tan, Xianliang; Wei, Shouchao; Wu, Zimeng; Xiao, Liying; Luo, Baoming (Frontiers in Immunology, 2025)
BackgroundImmunotherapy has made remarkable achievements in cancer treatment, but it still faces the challenge of limited response rates in liver cancer therapy. Although there has been extensive research on the role of programmed cell death-ligand 1 (PD-L1) in hepatocellular carcinoma (HCC), our understanding of the effects of other inhibitory B7/CD28 family members is still limited despite advancements in prognostic tools, more specific, accurate, and robust biomarkers are required to improve HCC patient prognoses.MethodsWe acquired the single-cell sequencing data from relevant literature and selected 42 liver tissue samples, including 89,246 cells from HCC patients, to investigate the expression, localization, and intercellular communications of the B7/CD28 family in HCC. Within the Cancer Genome Atlas dataset, we utilized Lasso and Cox regression analyses to develop a risk model for identifying the most pertinent B7/CD28 family proteins associated with prognosis. Subsequently, we conducted a retrospective analysis of 94 HCC patients who underwent hepatectomy at our institution and determined the prognostic significance of this malignancy.ResultsBased on the single-cell RNA sequencing data, we have delineated various members of the B7/CD28 family and their corresponding receptors. We have elucidated their distribution on tumor cells and immune cells, revealing active intercellular communications among tumor cells, fibroblasts, and epithelial cells. Through the implementation of Lasso, we have pinpointed a significant correlation between the B7H3 molecule and prognosis. Leveraging multiplex immunofluorescence, we were able to discern three distinct patterns of B7H3 expression—tumor-associated, stroma-associated, and a hybrid form encompassing both. Notably, the presence of B7H3 in the stroma exhibited the most robust correlation with prognosis. Furthermore, the efficacy of our prognostic signature was validated through clinicopathological analyses conducted at our institution.ConclusionsIn conclusion, the B7/CD28 family plays an active role in the tumor immune microenvironment and cellular communication. B7H3 could serve as an indicator for predicting the outcome of HCC. Additional investigation is required to validate these discoveries in future groups of individuals and assess their viability as therapies guided by biomarkers.